ADAPTATION PATTERNSTO DROUGHT OF TAMODE COMMUNITY IN TAMODE DISTRICT PATTALUNG PROVINCE - Tanongsak, Waraphorn (Journal of MCU Nakhondhat, 2021)
The Objectives of this research article were to the drought of Tamode community in Tamode District, Pattalung Province by conducting interview and organizing participatory brainstorming forum of core team members and farmer representatives. The results were found that there are 5 categories of agriculture consisting of paddy fields, rubber farms, fruit farms, field crops and pasturage.The main water source of paddy fields and fruit farms are derived from public canals, and there is a conflict from using water from late February to April which fruit farms use 216.21 - 294.36 cubic meters per month. In the past, farmers were trying to switch to grow other breeds of rice and less water use fruit trees, but it did not succeed, because these switched breeds did not suit for market demand, and there are some limitations of this area. Hence, stakeholders suggest suitable adaptation patterns to cope with the drought in this area with 3 phases consisting ofurgent phase (1 - 2 years) by sharing some water from KlongHuachang reservoir to Klonggong river, training farmers, government officers and private sections for adaptation to drought, building sources of underground water, establishing community water management system and rehabilitation of upstream forest. For medium phase (3 - 5 years) and long run phase (6 - 10 years) are maintenance of the water management system established from the urgent phaseto be efficient,and resulting from the rehabilitation of upstream forests willmakes it abundant and also plenty of water as well.